2007
DOI: 10.1007/s00221-007-1050-9
|View full text |Cite
|
Sign up to set email alerts
|

Some new prospects in the understanding of the molecular basis of the pathogenesis of stroke

Abstract: Stroke is one of the leading causes of mortality and morbidity in advanced countries of the world. Despite the fact that reactive oxygen and nitrogen species (ROS and RNS) are the by-products of normal metabolic processes and mediate important physiological processes, they can inflict damage to the cell if produced in excess due to oxidative stress. In the present review, we focus on the cellular and molecular aspects of ROS and RNS generation and its role in the pathogenesis of stroke produced by hypoxia-repe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
68
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(73 citation statements)
references
References 53 publications
0
68
0
2
Order By: Relevance
“…It is assumed that oxidative stress contributes to the initiation and development of stroke via different interrelated mechanisms [43]. Oxidative stress has a profound effect in stroke pathogenesis due to the high susceptibility of the brain to ROS-induced damage [44]. Independent of the mechanisms responsible for ischemic stroke, ischemia causes a cascade of events via different pathways that increase ROS production.…”
Section: Discussionmentioning
confidence: 99%
“…It is assumed that oxidative stress contributes to the initiation and development of stroke via different interrelated mechanisms [43]. Oxidative stress has a profound effect in stroke pathogenesis due to the high susceptibility of the brain to ROS-induced damage [44]. Independent of the mechanisms responsible for ischemic stroke, ischemia causes a cascade of events via different pathways that increase ROS production.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation can extend ischemic injury (20) to adversely affect stroke outcome (21) and may provide new therapeutic targets to treat patients outside of the narrow thrombolysis window of 3-6 h. For example, in a recent study it was shown that the administration of the drug AM-36, a Na ϩ channel blocker and an antioxidant, Histopathological analyses correspond to MPO imaging findings. (A) MPO imaging on day 3 after infarction shows a large area of enhancement in the basal ganglia and cerebral cortex.…”
Section: Discussionmentioning
confidence: 99%
“…ROS have significant cellular effects including lipid peroxidation, protein denaturation, inactivation of enzymes, nucleic acid and DNA damage, release of Ca 2+ from intracellular stores, damage to the cytoskeletal structure and chemotaxis. [28][29][30] On the other hand, MMP loss causes the release of apoptosis-inducing factors and generates secondary ROS, 31) and, as a result, ultimately leads to cell death. The research displayed that H 2 O 2 led to ROS production while ginkgolide K-pretreated significantly attenuated ROS level.…”
Section: Resultsmentioning
confidence: 99%